MODEL KEPEMIMPINAN DALAM LEMBAGA DAKWAH - Amelia, Rizki Lala; Castrawijaya, Cecep (Jurnal Al-Hikmah: Jurnal Dakwah, 2025)
Leadership is one of the important aspects in a da'wah institution, because an effective leader can influence the success and progress of the institution in achieving its goals. In the context of da'wah, leadership is not only about giving orders and supervising the implementation of tasks, but also about influencing and motivating members to achieve the goals that have been set. Da'wah institutions need leaders who can understand and apply the principles of Islamic leadership, as well as relevant leadership theories. Effective leaders in da'wah institutions must be able to combine various leadership styles wisely, adjusting to the needs and goals of the da'wah institution. These findings provide insight into the concept of leadership in da'wah institutions, including the principles of Islamic leadership and relevant leadership theories. In addition, various leadership styles that can be applied in da'wah institutions will also be discussed, as well as the importance of effective leadership in achieving the goals of da'wah institutionsKeywords: Leadership Model, Dakwah Management; Dakwah Institution.Kepemimpinan merupakan salah satu aspek penting dalam lembaga dakwah, karena pemimpin yang efektif dapat mempengaruhi keberhasilan dan kemajuan lembaga dalam mencapai tujuannya. Dalam konteks dakwah, kepemimpinan tidak hanya tentang memberikan perintah dan mengawasi pelaksanaan tugas, tetapi juga tentang mempengaruhi dan memotivasi anggota untuk mencapai tujuan yang telah ditetapkan. Lembaga dakwah memerlukan pemimpin yang dapat memahami dan menerapkan prinsip-prinsip kepemimpinan Islam, serta teori-teori kepemimpinan yang relevan. Pemimpin yang efektif dalam lembaga dakwah harus dapat memadukan berbagai gaya kepemimpinan dengan bijaksana, menyesuaikan dengan kebutuhan dan tujuan lembaga dakwah. Temuan ini memberikan wawasan tentang konsep kepamimpinan dalam lembaga dakwah, termasuk prinsip-prinsip kepemimpinan Islm dan teori-teori kepemimpinan yang relevan. Selain itu, juga akan dibahas tentang berbagai gaya kepemimpinan yang dapat diterapkan dalam lembaga dakwah, serta pentingnya kepemimpinan yang efektif dalam mencapai tujuan lembaga dakwah. Kata kunci: Model Kepemimpinan; Manajemen Dakwah; Lembaga Dakwah.